Protein-based engineering of the initial acquired enamel pellicle in vivo: Proteomic evaluation - Araújo, Tamara Teodoro; Carvalho, Thamyris Souza; Dionizio, Aline; Debortolli, Ana Luiza Bogaz; Ventura, Talita Mendes Oliveira; Souza, Beatriz Martines; Feitosa, Chelsea Maria Vilas Boas; Barbosa, Heloisa Aparecida Pereira; Ribeiro, Caroline Fernanda da Silva; Martini, Tatiana; Taira, Even; Shibao, Priscila Yumi Tanaka; et al. (Elsevier, 2022)
Objective: To study the proteomic alterations in the initial AEP after rinsing with CaneCPI-5, StN15 or Hb or their combination. Materials and methods: In five crossover phases, after prophylaxis, 10 volunteers in 5 consecutive days, rinsed (10 mL, 1 min) with the following solutions: deionized water (H2O- negative control- 1), 0.1 mg/mL CaneCPI-5 (2), 1.88×10−5 M StN15 (3), 1.0 mg/mL Hb (4) or their combination (5). The AEP formed after 3 min was collected with electrode filter papers soaked in 3% citric acid. After protein extraction, samples were analyzed by quantitative shotgun label-free proteomics. Results: Rinsing with the proteins/peptide increased the amounts of proteins in the AEP. The total numbers of proteins identified after rinsing with CaneCPI-5, StN15, Hb or their combination versus water, were 131, 167, 148 and 142, respectively. The treatment with the proteins/peptide or their combination increased proteins that bind calcium, phosphate and interact with distinct proteins, as well as proteins with antimicrobial and acid-resistant properties, such as, Cornifin-B (7.7, 12.6, and 4.3-fold for CaneCPI-5, StN15 and Hb, respectively), isoforms of Cystatin (2.2–2.4-fold for CaneCPI-5 and StN15), Proline-rich-protein 4 (4.3-fold; StN15), Histatin-1 (2.8-fold; StN15) and Hemoglobin (7.7–25-fold for Hb and Combination). Immunoglobulin, Keratin and Histone were exclusively identified upon treatment with the proteins/peptide, alone or combined. Conclusion: Rinsing with proteins/peptide, alone or combined, increased protective proteins in the initial AEP. Clinical Relevance: Our results suggest that rinsing with the proteins/peptide or their combination increases the proteins capable of enhancing the protective function of the basal layer of AEP.
Keywords: Acquired enamel pellicle; CaneCPI-5; Hemoglobin; Proteomics; Statherin